PENGARUH QUICK RATIO, EARNING PER SHARE, DAN RETURN ON INVESTMENT TERHADAP DIVIDEN KAS PADA PERUSAHAAN MANUFAKTUR SEKTOR FOOD AND BEVERAGES YANG TERDAFTAR DI BURSA EFEK INDONESIA - Amyas, Muhammad Arfan, Hasan Basri. (Jurnal Akuntansi, 2014)
Abstract: This study is aimed to examine and analyze (1) the effect of the quick ratio, earnings per share, and return on investment as simultaneously onthe cash dividends (2) the effect of the quick ratio onthe cash dividends (3) the effect of earnings per share on the cash dividend (4) the effect of the return on investment on cash dividends. The population in this study are 24 companies manufacturing sector, Food and Beverages in the Indonesia Stock Exchange that has a quick ratio, earnings per share, and return on investment and pay cash dividends. Time horizon used is a combination of the cross-sectional time series. This study uses census. To examine the effect of quick ratio, earnings per share, and return on investment of the cash dividend is used multiple linear regression models. Results of this study indicate that (1) simultaneously quick ratio, earnings per share, and return on investment have influence to the cash dividend. (2) quick ratio has a positive effect on cash dividends, (3) earnings per share has a positive effect on cash dividends, (4) return on investment positive effect on the cash dividend. Keywords: Quick ratio, earnings per share, return on investment, cash dividends Abstrak:Penelitian ini bertujuan untuk menguji dan menganalisis (1)pengaruh quick ratio,earning per share, dan return on invesmentsecara bersama-sama terhadap dividen kas(2) pengaruh quick ratio terhadap dividen kas (3) pengaruh earning per share terhadap dividen kas (4) pengaruh return on invesment terhadap dividen kas.Populasi dalam penelitian ini yaitu 24 perusahaan manufaktur sektor Food and Beverages di Bursa Efek Indonesia yang memiliki quick ratio, earning per share, dan return on investment serta membayarkan dividen kas. Horizon waktu yang digunakan adalah cross sectional dengan time series. Penelitian ini menggunakan metode sensus. Untuk menguji pengaruh quick ratio, earning per share, dan return on investment terhadap dividen kas digunakan model regresi linierberganda.Hasil penelitian ini menunjukkan bahwa (1) secara bersama-samaquick ratio, earning per share, dan return on investment berpengaruh positif terhadap dividen kas. (2) quick ratio berpengaruh positif terhadap dividen kas, (3) earning per share berpengaruh positif terhadap dividen kas, (4)return on investmentberpengaruh positif terhadap dividen kas. Kata Kunci: Quick ratio, earning per share, return on investment, dividen kas